Cardiac Tumors: A Brief Commentary - Roever, Leonardo; Casella-Filho, Antonio; Dourado, Paulo Magno Martins; Resende, Elmiro Santos; Chagas, Antônio Carlos Palandri (Frontiers in Public Health, 2014)
Patients with cardiac tumours may present with cardiovascular related or constitutional symptoms, but more often than not a cardiac mass is discovered incidentally during an imaging examination performed for an unrelated indication.Cardiac myxoma is generally considered to be a surgical emergency. Echocardiography, including the transesophageal approach, is the most important means of diagnosis; CT and MRI. The clinical presentation has changed and the management of cardiac myxoma now needs to be reviewed.